Ethanol-induced transformation of furfural into 1, 4-pentanediol over a Cu/SiO2 catalyst with enhanced metal–acid sites by copper phyllosilicate. Issue 3 (20th January 2023) - Zheng, Yanni; Zang, Jiaxuan; Zhang, Qian; Wu, Xiaoping; Qiu, Songbai; Meng, Qingwei; Wang, Tiejun
Abstract : Ethanol-induced one-pot transformation of furfural into 1, 4-pentanediol (1, 4-PeD). Abstract : Hydrogenolysis of the large-scale biomass-derived furfural to pentanediols (PeDs) is of great significance for resource saving and development of polyester monomers. In this work, a Cu/SiO2 catalyst derived from copper phyllosilicate with enhanced metal–acid sites was developed, which demonstrated distinctive catalytic activity in the ethanol-induced conversion of furfural into 1, 4-pentanediol (1, 4-PeD). A significant yield of 1, 4-PeD (86.2%) was obtained over the Cu/SiO2 catalyst without the addition of any solid or homogeneous acid at a mild temperature (120 °C). Different from the previously reported reaction routes, our work proposed a novel ethanol-induced conversion route via acid-catalyzed etherification of furfuryl alcohol and ethanol to form 2-ethoxymethyl-furan (2-(EoM)F) as the key intermediate, which followed the degradation to ethyl levulinate (EL) and hydrogenation to 1, 4-PeD over metal sites. This work describes an important progress in this field by developing an efficient strategy for ethanol-induced transformation of furfural into 1, 4-PeD.